Raziskava vpliva naprave za magnetno obdelavo vode na izločanje vodnega kamna v industrijskem stroju za pomivanje steklenic z uporabo vrstične elektronske mikroskopije - Kozic, Viljem (Strojniški vestnik, 2004)
A commercial magnetic device for scale control was tested in an industrial machine for bottle cleaning. Scale samples, which had precipitated on test plates of different materials, were compared for magnetically treated and non-treated water. Gravimetrical results and morphological-chemical results from a scanning electron microscope analysis showed practically the same chemical composition, but an approximately 20% decrease in the amount of scaleand less-compact, non-adhesive, powder-like structures in the cases of magnetically treated water. In the case of precipitation on a corrosive steel plate, the magnetic treatment caused the abundant formation of iron hydroxide,but the structure of the precipitate was also less compact than in the other cases.
Keywords: obdelava vode magnetna; kamen vodni; mikroskopi elektronski; mikroskopi vrstični; vodni kamen; mehčanje vode; pomivalni stroji; elektronska mikroskopija